Clinical utility of lanreotide Autogel® in gastroenteropancreatic neuroendocrine tumors - Paragliola RM; Prete A; Papi G; Torino F; Corsello A; Pontecorvi A; Corsello SM (Dove Medical Press, 2016)
Rosa Maria Paragliola,1 Alessandro Prete,1 Giampaolo Papi,1 Francesco Torino,2 Andrea Corsello,3 Alfredo Pontecorvi,1 Salvatore Maria Corsello1 1Department of Medicine, Unit of Endocrinology, Università Cattolica del Sacro Cuore, 2Department of Systems Medicine, Tor Vergata University, Rome, 3Department of General Medicine and Endocrine Tumor Unit, San Raffaele Scientific Institute, Milan, Italy Abstract: Somatostatin analogs (SSAs), which were initially used to control hormonal syndromes associated with neuroendocrine neoplasms (NENs), have been successfully proposed as antiproliferative agents, able to control tumor growth in patients affected by gastroenteropancreatic (GEP)-NENs. The development of long-acting formulations of SSAs which require only weekly or monthly injections can improve patient compliance. In particular, lanreotide (LAN) Autogel®, which is a viscous aqueous formulation supplied in ready-to-use prefilled syringes, can be administered every 28–56 days. Since its introduction in the clinical practice, several studies evaluated the clinical utility of LAN Autogel in the medical treatment of GEP-NENs. Although there is no evidence of an overall survival benefit, these studies confirm the efficacy of LAN Autogel in terms of benefit in progression-free survival, and in more than half of cases, a reduction of tumor markers can be observed during treatment with this drug. Moreover, LAN Autogel is widely recognized to be effective in controlling tumor-related symptoms in the majority of patients affected by GEP tumors, especially in patients affected by carcinoid syndrome, improving considerably patients’ quality of life. Keywords: lanreotide Autogel, gastroenteropancreatic neuroendocrine tumors, gastroenteropancreatic neuroendocrine neoplasms, somatostatin analogs